Phase II trial of single‐agent panobinostat consolidation improves responses after sub‐optimal transplant outcomes in multiple myeloma. (18th September 2020) - Mithraprabhu, Sridurga; Kalff, Anna; Gartlan, Kate H.; Savvidou, Ioanna; Khong, Tiffany; Ramachandran, Malarmathy; Cooke, Rachel E.; Bowen, Kathryn; Hill, Geoffrey R.; Reynolds, John; Spencer, Andrew
Summary: Panobinostat is a pan‐deacetylase inhibitor that modulates the expression of oncogenic and immune‐mediating genes involved in tumour cell growth and survival. We evaluated panobinostat‐induced post‐transplant responses and identified correlative biomarkers in patients with multiple myeloma who had failed to achieve a complete response after autologous transplantation. Patients received panobinostat 45 mg administered three‐times weekly (TIW) on alternate weeks of 28‐day cycles commencing 8–12 weeks post‐transplant. Twelve of 25 patients (48%) improved their depth of response after a median (range) of 4·3 (1·9–9·7) months of panobinostat. In responders, T‐lymphocyte histone acetylation increased after both three cycles ( P < 0·05) and six cycles ( P < 0·01) of panobinostat when compared to baseline, with no differences in non‐responders. The reduction in the proportion of CD127 + CD8 + T cells and CD4:CD8 ratio was significantly greater, after three and six cycles of panobinostat compared to pre‐transplant, in non‐responders when compared to responders. Whole marrow RNA‐seq revealed widespread transcriptional changes only in responders with baseline differences in genes involved in ribosome biogenesis, oxidative phosphorylation and metabolic pathways. This study confirmed the efficacy of panobinostat as a single agent in multiple myeloma and established acetylation of lymphocyte histones, modulation of immune subsets and transcriptional changes as pharmacodynamic biomarkers of clinical benefit.